Open reduction and internal fixation: Screw injury - Retrospective study - Preetha Balaji; S M Balaji (Wolters Kluwer Medknow Publications, 2017)
Background/Aims: Open reduction and internal fixation (ORIF) is a standard surgical procedure in jaw trauma and in orthognathic surgery. Insertion of screws is a significant risk for accidental tooth root injury with varying outcomes. Contrary evidences are found in literature due to a variety of study designs. This study was undertaken to address the lacunae and possibly estimate the difference in occurrence of tooth damage during or after ORIF between trauma and planned osteotomies. Materials and Methods: In this retrospective study, the data of ORIF in either trauma or orthognathic surgery fulfilling inclusion and exclusion criteria were collected and analyzed. Results: There were 1632 patients fulfilling the inclusion and exclusion criteria and formed the study group, of which 663 were in orthognathic surgery, of whom 210 had bimaxillary orthognathic surgery. In the trauma group, 358 patients had fractures involving both jaws whereas 272 had maxilla alone and 339 had mandibular fractures alone. On comparing the outcome, of the 9073 screws studied, 93.40% were not involved in any contact with the teeth, 6.3% were in category of potential hits (near apices or the root surfaces), and only 0.28% had evidence of root damage with the screws. It is observed that molar and premolar had a significant difference in terms of the type of surgery (P ≤ 0.05) whereas canine (P = 0.75) and incisor (P = 0.67) showed no statistical difference. Conclusion: ORIF when used as mentioned is a safe way for the management of fractures. The incidence of root injury is not uncommon but can be avoided with careful planning and execution.